Safety of basal-bolus versus premixed insulin intensification regimens in the management of type 2 diabetes mellitus: a narrative review of a 14-year experience - Penwalla, Nazia I,; Othman, Noordin; Mohamed Nazar, Nor Ilyani; Nik Ahmad, Nik Nur Fatnoon (Production and Hosting by Elsevier Ltd. on behalf of Taibah University, 2015)
Objectives: The best insulin regimen for the intensification of insulin therapy in the management of type 2 diabetes mellitus (T2DM) remains controversial. Despite substantial research, the body of evidence concerning the safety aspects of such regimens has never been summarized. We conducted a 14-year narrative review to compare the safety outcomes of basal-bolus (BB) versus premixed (PM) insulin regimens. Methods: We searched electronic databases (PubMed, Scopus, Proquest and Google Scholar) for English language studies published from January 2000 to December 2014 to identify studies comparing insulin intensification regimens. Only studies measuring the safety-related parameters of the specific regimens in T2DM adult patients were selected for further review. The extracted data were independently reviewed by two researchers, and disagreements were resolved by discussion. Results: Of the 20 retrieved studies, we included 10 studies that specifically compared the safety parameters of BB and PM Insulin regimens. Among the safety outcomes measured were hypoglycaemia, weight gain and adverse events. Broadly, we determined that the BB insulin regimens were comparable to the PM insulin regimens in terms of hypoglycaemia and adverse events. In terms of weight gain, two of seven studies showed significant weight gain in BB insulin regimen arms. Conclusions: Generally, the safety profile of BB insulin regimen was comparable to that of the PM insulin regimen. None of the identified studies performed headto- head comparisons utilizing human insulin regimens in both arms. Research comparing non-analogue insulin regimens is warranted.